Associations between socioeconomic position and changes in children's screen-viewing between ages 6 and 9: a longitudinal study. Issue 12 (10th December 2019) - Salway, Ruth E; Emm-Collison, Lydia; Sebire, Simon; Thompson, Janice L; Jago, Russ
Abstract : Objectives: To explore socioeconomic differences in screen-viewing at ages 6 and 9, and how these are related to different media uses. Design: Longitudinal cohort study. Setting: Children recruited from 57 state-funded primary schools in Southwest England, UK. Participants: 1299 children at ages 5–6, 1223 children at ages 8–9, including 685 children at both time points. Outcome measures: Children's total screen-viewing time (parent-reported) and time spent using multiple screen devices simultaneously (multiscreen viewing), for weekdays and weekends. Methods: Negative binomial regression was used to model associations between socioeconomic variables (highest household education and area deprivation) and total screen-viewing at age 6 and the change from age 6 to 9. We additionally adjusted for child characteristics, parental influences and media devices in the home. Multiscreen viewing was analysed separately. Results: Household education was associated with children's screen-viewing at age 6 with lower screen-viewing in higher socioeconomic groups (21%–27% less in households with a Degree or Higher Degree, compared with General Certificate of Secondary Education: GCSE). These differences were explained by the presence of games consoles, parental limits on screen-viewing and average parent screen-viewing. Between ages 6 and 9, there were larger increases in screen-viewing for children from A level and Degree households (13% and 6%, respectively, in the week) and a decrease in Higher Degree households (16%), compared with GCSE households. Differences by household education remained when adjusting for media devices and parental factors. Conclusions: Children's screen-viewing patterns differ by parental education with higher levels of viewing among children living in households with lower educational qualifications. These differences are already present at age 6, and continue at age 9. Strategies to manage child sedentary time, and particularly screen-viewing, may need to take account of the socioeconomic differences and target strategies to specific groups.